2019
DOI: 10.1155/2019/1875471
|View full text |Cite
|
Sign up to set email alerts
|

Atractylenolide III Attenuates Muscle Wasting in Chronic Kidney Disease via the Oxidative Stress-Mediated PI3K/AKT/mTOR Pathway

Abstract: Oxidative stress contributes to muscle wasting in advanced chronic kidney disease (CKD) patients. Atractylenolide III (ATL-III), the major active constituent of Atractylodes rhizome, has been previously reported to function as an antioxidant. This study is aimed at investigating whether ATL-III has protective effects against CKD-induced muscle wasting by alleviating oxidative stress. The results showed that the levels of serum creatinine (SCr), blood urea nitrogen (BUN), and urinary protein significantly decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 54 publications
3
60
0
Order By: Relevance
“…Currently, increasing evidences have suggested that the PI3K/AKT signal pathway plays a crucial role in cell survival and development as well as ROS-induced cell apoptosis [40,41]. In addition, the PI3K/AKT pathway shows significant antioxidant activity in central and peripheral neurons and can be considered a potential therapeutic target for neurodegenerative diseases, participating in the cellular protective mechanism of ROS-induced cell damage [39].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, increasing evidences have suggested that the PI3K/AKT signal pathway plays a crucial role in cell survival and development as well as ROS-induced cell apoptosis [40,41]. In addition, the PI3K/AKT pathway shows significant antioxidant activity in central and peripheral neurons and can be considered a potential therapeutic target for neurodegenerative diseases, participating in the cellular protective mechanism of ROS-induced cell damage [39].…”
Section: Discussionmentioning
confidence: 99%
“…Bai Zhu is commonly used to invigorate the spleen to regulate water in kidney, according to CHM theory. Studies have demonstrated that Atractylodes macrocephala can reduce chronic kidney disease-induced inflammation and muscle atrophy by inhibiting the PI3K-Akt pathway ( Wang et al, 2019a , Wang et al, 2019b ). At the same time, it can reduce the production of proinflammatory mediators NO, reduce the levels of TNF and IL, and then relieve the damage of renal cells ( Ishii et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, for drug-induced renal injury, it has been shown that Huang Qi can protect against gentamicin-induced renal injury by inhibiting oxidative stress response and inflammatory factors ( Wang et al, 2019a , Wang et al, 2019b ). The triterpenoids extracted from Fu Ling have protective effects on cisplatin nephrotoxicity, and the mechanism is related to the anti-apoptotic activity of the ingredients ( Lee et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…[36][37][38] Chrysin reportedly inhibited inflammation and decreased IL-1β, TNF-α, and IL-6 levels by activating the PI3K/AKT/ mTOR pathway. 38 Wang et al 39 The phosphorylation of IκBa by IKK triggers a signal for the ubiquitination and degradation of IκBa followed by activation of NF-κB. 40 Activation of NF-κB by IKK also occurs in association with reactive oxygen species (ROS) produced by NADPH oxidase in response to activation of receptors, such as IL-1 or TNF.…”
Section: Discussionmentioning
confidence: 99%